2022
DOI: 10.1093/jacamr/dlac044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring barriers to guideline implementation for prescription of surgical antibiotic prophylaxis in Nigeria

Abstract: Background In Nigeria, the prescription of surgical antibiotic prophylaxis for prevention of surgical site infection tends to be driven by local policy rather than by published guidelines (e.g. WHO and Sanford). Objectives To triangulate three datasets and understand key barriers to implementation using a behavioural science framework. Methods Surgeons (N = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…28 Another study that examined adherence to mammographic recommendations in the US found that fear of missing cancer diagnoses and malpractice were behind screening practices that differed from age and intervals recommended in guidelines. 29 In their analysis of factors in uencing adherence to antibiotic prescription guidelines, Wood et al 30 pointed out that strategies to increase guidelines utilization should train HPs so they feel empowered and have con dence that they are implementing best practice in line with international standards whilst at the same time maintaining safety of their patients. For Wood et al, 30 this requires awareness raising of the consequences resulting from prescription outside of guideline recommendations, knowledge building of the recommendations set out in guidelines and training provision on how they can be adapted to context.…”
Section: Discussionmentioning
confidence: 99%
“…28 Another study that examined adherence to mammographic recommendations in the US found that fear of missing cancer diagnoses and malpractice were behind screening practices that differed from age and intervals recommended in guidelines. 29 In their analysis of factors in uencing adherence to antibiotic prescription guidelines, Wood et al 30 pointed out that strategies to increase guidelines utilization should train HPs so they feel empowered and have con dence that they are implementing best practice in line with international standards whilst at the same time maintaining safety of their patients. For Wood et al, 30 this requires awareness raising of the consequences resulting from prescription outside of guideline recommendations, knowledge building of the recommendations set out in guidelines and training provision on how they can be adapted to context.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance has been reported to be largely human-driven and prescribers in healthcare facilities are not absolved, more so in developing countries such as Nigeria, where inappropriate prescribing practices by clinicians have been recognized contributors [2] [4] [7]. Inappropriate prescription practices which occur at both in-patient and outpatient settings include the use of wrong dosages, dosing intervals and duration of treatment, use of antibiotics when there is no bacterial infection, and overuse of newer, broad-spectrum antibiotics when either no antibiotic or an older narrow-spectrum drug would be sufficient as well as use of ineffective antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…The high patient to doctor ratio in Nigeria, particularly in public health institutions also is a contributory factor, in that, the clinicians are usually overwhelmed and so unable to take the time to properly counsel patients on appropriate antimicrobial usage [7] [8] [9]. Physicians' attitudes of self-approval, lack of information, apathy, fear of adverse treatment outcomes (including losing patronage and litigation), autonomy of practice and refusal to accept responsibility to prescribe antibiotics appropriately have also been well noted to promote inappropriate prescribing patterns among clinicians [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our pilot, 25% of AB were prescribed without clear indication. There are many reasons for prescribing antibiotics against standardized guidelines (20). There is a lack of oversight, as antimicrobial stewardship programmes in Nigerian hospitals are inadequate (26) and if present, guidelines are being weakly enforced (27).…”
Section: Understanding the Drivers Of Ab Overprescribingmentioning
confidence: 99%